Justicia anselliana (Nees) T. Anders Essential Oils Compounds and Allelopathic Effects on Cowpea Vigna unguiculata (L.) Walp Plant - KPOVIESSI DOSSOU, SIKA SALOME; GBENOU, Joachin D.; Gbaguidi, A. Fernand; Ahoussi, Léon; Accrombessi, Georges C.; MOUDACHIROU, MANSOUROU; Quetin-Leclercq, Joëlle (My University, 2009)
Analysis of Justicia ancelliana essential oils by GC and GC/MS revealed the presence of b-phellandrene (51.2%), d-2-carene (43.4%), dihydrotagetone (0.4%), propyl butyrate (0.3%) in the aerial parts and phenylacetaldehyde (39.2%), d-3-carene (31.7%), 6-methyl-5-hepten-2-one (16.4%) and a-phellandrene (12.6%) in the roots. These oils and their compounds induced a reduction in the growth of the roots, the apparition of yellow leaves after two weeks of the treatment and the death of the Vigna unguiculata young plants and showed a specific action on the germination and the growth of Zea mays, Vigna unguiculata and Arachis hypogeae plants. b-Phellandrene and phenylacetaldehyde showed maximum inhibition to germination and growth of Vigna unguiculata.
Keywords: Justicia anselliana; essential oil composition; Vigna unguiculata; allelopathy